Machine perfusion in kidney transplantation. Issue 4 (August 2019) - Kataria, Ashish; Magoon, Sandeep; Makkar, Binni; Gundroo, Aijaz
Abstract : Purpose of review: The shortage of kidneys for transplantation has led to an urgent need to efficiently utilize the available cadaveric kidneys. Efficient use of machine perfusion may potentially lead to increased use of marginal kidneys by lowering the incidence of delayed graft function (DGF) and improving graft outcomes. Recent findings: Machine perfusion has had a resurgence in the last 10–15 years over static cold storage (SCS). Hypothermic machine perfusion (HMP), the most commonly utilized type of machine perfusion reduces the rates of DGF when compared with SCS with a trend towards improving the overall graft survival. Summary: Despite reduction in the rates of DGF by HMP, its effect on long-term renal and patient outcomes is not clearly known. There is limited clinical literature in the use of normothermic machine perfusion (NMP) but a few pilot studies have shown its potential to resuscitate commonly discarded kidneys. In addition to preservation, machine perfusion also allows for various diagnostic and therapeutic interventions during the preservation period to assess and optimize the viability of the procured kidney.